Service quality survey for Sarawak Forestry Corporation / Nagarajah Lee Hun Leong... [et al.] - Lee Hun Leong, Nagarajah; Boo Ho, Voon; Abdullah, Firdaus; Deen, Abdul Rahman; Seh Ling, Iris Syawe; Maghar Singh, Baljinder (2005)
Service quality has attracted considerable attention within the service sectors, and it is considered as the most formidable competitive trend currently shaping business strategies. In today's highly competitive business environment, rendering consistent excellent service is a key for survival and success. Sarawak Forestry Corporation (SFC) is undoubtedly among the early pioneer organisations in Sarawak to undertake a large-scale exercise using multiple approaches to improve the quality of its services towards organisational excellence. Supported by solid management commitment and dedication through its vision of being a global and recognised leader in tropical forest conservation and products, coupled with the values 'I CARE' (Integrity, Customer focused, Accountable, Recognition for performance and Environment stewardship), service quality is certainly a key strategic issue on SFC's noble agenda. Indeed, one of the most critical issues associated with service provision is the assessment of service quality, particularly due to its relationship to financial performance, customer satisfaction, customer retention and competitive advantage. The pressures driving successful organisations towards excellent service make the measurement and the subsequent management of service quality a top priority. Although various measuring instruments have been used to capture the customers' perceptions of service quality within a specific industry, in this study, the SERVQUAL was adapted to cater exclusively for the unique forest conservation Setting.